Prinsip Pendidikan Islam Perspektif Omar Mohammad Al-Toumy Asy-Syaibani - Helmy Abdullah Helmy; Mhd. Aksaril Huda Ritonga; Rosmayati Rosmayati; Salma Rahma Dina; Muhamad Parhan; Syahidin Syahidin (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Principles of Islamic Education Omar Mohammad Al-Toumy Al-Syaibani's views reflect the philosophical basis of education in Islam. According to Asy-Syaibani, education is based on the principles of monotheism, the Koran and Hadith, with an emphasis on forming a personality with noble character. Furthermore, Islamic education, in his view, combines knowledge about the world, promotes social justice, and maintains balance between religion and the world. Intercultural cooperation is also an important value in this educational model. These principles provide a foundation for the development of individuals who have faith and integrity and play an active role in building a better society.